2022
DOI: 10.3390/polym14173458
|View full text |Cite
|
Sign up to set email alerts
|

Study of Blast Mitigation Performance and Fracture Mechanism of Polyurea under Contact Explosion

Abstract: In order to further study the blast mitigation performance of polyurea and to investigate the protection mechanism and damage characteristics of polyurea-protected structures under contact explosion loads, based on earlier work, this paper investigated the response and energy absorption performance of polyurea under various frequency loads. Qtech T26 blast mitigation polyurea (T26 polyurea) was adopted to protect the reinforced concrete (RC) slab and damage analysis of the post-explosion specimens was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Sun et al [40] observed an increased absorption of localized impact energy at approximately 115 • C, which corresponds to the transition temperature from the glassy to the rubbery state when subjected to high-speed dynamic loading. Notably, materials that exhibit a wider temperature range in the glass transition zone and lower microphase segregation demonstrate superior flexibility and energy absorption under high strain rate loading conditions [41,42].…”
Section: Hydrogen Bond Dissociation and Reorganization Rearrangement ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Sun et al [40] observed an increased absorption of localized impact energy at approximately 115 • C, which corresponds to the transition temperature from the glassy to the rubbery state when subjected to high-speed dynamic loading. Notably, materials that exhibit a wider temperature range in the glass transition zone and lower microphase segregation demonstrate superior flexibility and energy absorption under high strain rate loading conditions [41,42].…”
Section: Hydrogen Bond Dissociation and Reorganization Rearrangement ...mentioning
confidence: 99%
“…Upon impact, the ordered arrangement of the hard segments is disrupted, resulting in a reduction in the number of hydrogen bonds. The dissociation of hydrogen bonds leads to a substantial increment in the potential [41,46]. Additionally, the soft phase stores a greater amount of strain energy compared to the hard phase under impact.…”
Section: Hydrogen Bond Dissociation and Reorganization Rearrangement ...mentioning
confidence: 99%
See 3 more Smart Citations